PERTANGGUNGJAWABAN PIDANA INFLUENCER DALAM PENIPUAN DENGAN MODUS APLIKASI TRADING - Supriadi, Supriadi (Journal Economics Technology And Entrepreneur, 2024)
This study aims to determine and analyze the role of Influencers in fraud with the Trading Application mode and analyze the criminal liability of Influencers in fraud with the Trading Application mode. Researcher goes directly to the research location to collect data by conducting interviews besides that in this research the library research method. The results of the research conducted by the author found that the influencer's role in promoting fraudulent trading applications is that the Influencer acts as an Affiliator. Influencers utilize online media as a means for the perpetrators to find targets to be interested in investing as the term is known today. With the lure of fantastic results by capitalizing quite minimal money, the victims have been promised to gain profits. The criminal liability of influencers for investment fraud in the crime of investment trading fraud only includes imprisonment and fines. While the aspect of compensation for victims of fraud is only related to the scope of civil, not criminal. Regarding the protection of victims of investment trading fraud, the implementation often experiences obstacles in the prosecution process.